English in Higher Education Context: A Comparative Study of Indonesia and Thailand Students - Hadiati, Chusni; Nur Kholifah, Asrofin; Ardhanariswari, Riris (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
English grows fast in Southeast Asia due to the importance of it as the language of modernization and international communication. Thailand and Indonesia are both located in Southeast Asia with their own national language, Thai and Bahasa Indonesia and thus English in both countries functions as a foreign language. This research tries to reveal English in higher education context by focusing on university students’ perception on English. The respondents of this research are the student of Jenderal Soedirman University and Burapha University It investigated 120 students consisting 30 male Indonesia students, 30 female Indonesia students, 30 male Thailand students, and 30 female Thailand students. Several aspects are investigated to capture students’ perception based on the following aspects (1) students perception on English as a compulsory subject, (2) students’ preference on their English teacher, (3) English hour in university, (4) the level of difficulties of English features, and (5) students’ preferable ways to improve their English.